بروتين المرحلة الحادة للإلتهاب (CRP) كمنبئ للوفيات القلبية الوعائية عند مرضى التحال الدموي - لايقة, عنان (Latakia University Journal -Medical Sciences Series, 2018)
objective: to establish and examined associations of C-reactive protein (CRP) levels that would predict increased overall and cardiovascular mortality in patients with end-stage renal disease . Methods. A cohort of 58 prevalent hemodialysis patients treated at teshreen University Hospital, was eligible for the study. CRP, albumin , creatinin ,urea and hemoglobin , measurements were performed for two consecutive months. . During the one-year follow-up, 12 patients died The most frequent cause of death was cardiovascular. CRP baseline concentration correlates well( 85%) with mortality in patients with ESRD . In conclusion, the current study findings suggest that CRP as a prototypical acute phase protein in humans is a strong predictor of overall and cardiovascular mortality in patients with ESRD. إن هدف هذه الدراسة هو تقييم و فحص العلاقة ما بين ارتفاع ( CRP ) المصل و التنبؤ بالوفيات القلبية الوعائية عند مرضى التحال الدموي. 58 مريضا موضوعين على التحال الدموي في مشفى تشرين الجامعي , حيث تم معايرة (CRP )المصل , الألبومين, كرياتينين المصل , البولة الدموية , و خضاب الدم . و تمت متابعتهم لمدة عام كامل , من حيت الوفيات و الحوادث القلبية الوعائية . النتائج أظهرت : 12 مريضا توفوا , و أن 85% من المرضى الذين توفوا كان لديهم ارتفاع في مستوى CRP المصل , و أن الحوادث القلبية الوعائية هي من أكثر أسباب الوفيات حدوثا. إن نتائج هذه الدراسة تظهر أن ارتفاع بروتينات المرحلة الحادة للإلتهاب CRP, هو منبئ قوي للوفيات القلبية الوعائية عند مرضى القصور الكلوي النهائي .